PEMBINAAN USAHA KECIL KERAJINAN TENUN SONGKET OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU - Madona "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine how a small business coachingSongket Weaving craft carried out by the Department of Industry and TradePekanbaru City and to determine what factors are an obstacle in the development ofsmall businesses Songket weaving handicrafts made by the Department of Industryand Trade Pekanbaru. The methodology of this research consists of the researchsites, informants research, types and sources of data, engineering data collection,and data analysis. Analysis of the data used in this study is a qualitative descriptiveanalysis method which gives a clear picture in detail based on the data that wascollected in the field through the interviews were then drawn a conclusion. Thesurvey results revealed that small business coaching Songket Weaving craft is notmaximized due to lack of funding from the government budget, the limited number ofextension staff (functional) in the Department of Industry and Trade of Pekanbaru,conducive business climate is not maximized, the limited of infrastructure, humanresources limited, access to marketing, mastery of technology and a lack ofpromotion of the government.Keywords: Coaching, Small Business, Craft , Songket Weaving